Neuroprotective Effects of Qingnao Dripping Pills Against Cerebral Ischemia via Inhibiting NLRP3 Inflammasome Signaling Pathway: In Vivo and In Vitro - Fu, Chen; Zhang, Xinyang; Zeng, Zixiu; Tian, Yang; Jin, Xianglan; Wang, Fengli; Xu, Zhenmin; Chen, Baoxin; Zheng, Hong; Liu, Xuemei (Frontiers in Pharmacology, 2020)
Ischemic stroke patients suffer from relatively limited treatment options. Studies have shown that in cerebral ischemia, NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is a key mediator in mediating inflammatory responses and result in activation of apoptosis signaling pathways. Here we assessed the in Vivo and in Vitro effects of Qingnao Dripping Pills (QNDP), a traditional Chinese prescription, on inflammatory responses and apoptosis. Our results showed that QNDP could significantly decrease cerebral ischemia injury and improve neurological function in rats impaired by middle cerebral artery occlusion (MCAO). Further, we found that QNDP inhibits apoptosis and NLRP3 inflammasome expression after cerebral Ischemia. Moreover, the levels of inflammatory cytokines including interleukin-1β (IL-1β) and IL-18, which mediated by NLRP3 inflammasome and increased in MCAO rats, could be reduced by QNDP, suggesting that QNDP could protect the neurons against inflammation through a mechanism mediated by NLRP3 inflammasome. Nuclear factor-kappa B(NF-κB) was also involved in the anti-inflammatory effect of QNDP. In conclusion, QNDP had neuroprotective effects against cerebral ischemia via inhibiting NLRP3 inflammasome signaling pathway, and was a potential candidate for the future treatment of ischemic stroke.